Peran Kepala Sekolah Dalam Meningkatkan Kinerja Guru Melalui Supervisi Klinis Di SMPN 3 Keruak - Sopiatun, Sopiatun; Subhani, Armin; Fahrurrozi, Muh (Universitas Hamzanwadi, 2024)
This research aims to determine the role of the school principal in implementing clinical supervision which has an impact on teacher performance in carrying out teaching and learning activities. This research uses a qualitative descriptive approach by studying the facts that occurred, data collection techniques were obtained through interviews with school principals and teaching staff. direct observation and documentation studies. Clinical supervision is really needed by teaching staff to improve professional teacher performance. Through clinical supervision, school principals can provide guidance related to increasing the competency of teaching staff in carrying out learning in the classroom. Clinical supervision carried out by the principal at SMP Negeri 3 Keruak is carried out in stages which globally consist of pre-observation meetings, classroom observations and feedback or post-observation meetings. As well as follow-up evaluation. This research is a type of descriptive research using a descriptive approach. The method used in this research is a descriptive qualitative method. This research was carried out at SMP Negeri 3 Keruak. The data collection techniques used are observation, interviews and documentation. The results of this research show that clinical supervision can improve teachers' abilities in implementing the learning process at SMP Negeri 3 Keruak. This can be seen from the results of observations which show the teacher's score is above 80 in the good category. From the results of interviews after carrying out clinical supervision, it shows that they feel happy after getting feedback from the school principal so that they can identify weaknesses in the learning process.